Immunostimulatory effect of kumquat (Fortunella crassifolia) and its constituents, β-cryptoxanthin and R-limonene. Issue 1 (14th December 2018) - Terao, Rina; Murata, Akira; Sugamoto, Kazuhiro; Watanabe, Tomoko; Nagahama, Kiyoko; Nakahara, Keiko; Kondo, Tomomi; Murakami, Noboru; Fukui, Keiichi; Hattori, Hidemi; Eto, Nozomu
Abstract : The active constituents of kumquat in NK cell activation and anti-stress effects are β-cryptoxanthin and R -limonene. Abstract : Natural killer (NK) cells play an important role in the innate immune system by eliminating cancer cells and virally infected cells. Aging and stress attenuate the activity of NK cells, thereby increasing the risk of various diseases. In this study, we demonstrated that the consumption of a small number of kumquats in an in vivo model could suppress elevated plasma corticosterone levels and reverse the decline in splenocyte cytotoxicity caused by restraint stress. Our results identified β-cryptoxanthin (BCX) as an active kumquat component with a NK cell-activating effect, and R -limonene as an active component that mediates not only the anti-stress effect but also NK cell activation by oral administration. In addition, BCX, R -limonene, and R -limonene metabolites were found to enhance IFN-γ production in KHYG-1 cells, a human NK cell line. Collectively, our findings suggest that the ingestion of a few kumquats on a daily basis can help to combat stress and enhance NK cell activity.